Perception of Students towards School Principals’ Effectiveness in Improving their Achievement: A Case Study of Secondary Schools in Zomba District, Malawi - Elizabeth, Piliyesi (African Journal of Education,Science and Technology (AJEST), 2015)
The research aimed to find perception of students towards school principals‘ effectiveness in improving their achievement in secondary schools in Zomba District of Malawi. The target population consisted of the all the students in government and private schools in Zomba District. The researcher employed stratified sampling to sample 12 secondary schools. The respondents comprised of 168 students. The researcher used questionnaire for collecting data. Descriptive statistics were used in data analysis. The results indicated that highest proportion of the students viewed the school principals as ineffective since they don‘t struggle to provide adequate facilities to make leaning smooth. In addition, they rarely encourages maximum utilization of learning materials, rarely provide enough teaching and learning materials, rarely encourage teachers to provide remedial classes, rarely accepts opinion from students. The study recommends that, for the school principals to be effective, they should actively be involved in classroom observations; should meet with the teachers often and ensure that teachers are implementing the actual curriculum. Principals should also involve the students in the decision making processes in the school. This will give the students an avenue to air their views which are crucial in formulation of school policies.